PROFIL RESILIENSI REMAJA PANTI ASUHAN DAN IMPLIKASINYA BAGI LAYANAN BIMBINGAN PRIBADI DAN SOSIAL - Syifa Nur Shofwah, - (2021)
The research background is based on the importance of resilience ability for adolescents because in this situation adolescents living in orphanages experience several special challenges that are different from their peers. In these conditions, psychological resilience, the ability of individuals to rise from adversity, is really needed to help them overcome the problems they face. Resilience provides the capacity to overcome difficulties and turn them into opportunities for growth. By developing resilience skills, the adolescents in the orphanage assess the benefits of living in an orphanage that can help them adjust well after past experiences / past failures. The research objective was to obtain empirical data regarding the resilience profile of adolescents in orphanages, and to produce personal and social guidance services in optimizing the resilience of adolescents in orphanages. Data collection used the CYRM-R (The Child and Youth Resilience Measure-Revised) instrument. The research used a quantitative approach with descriptive research methods, the design used in the study was a survey. The study population was all adolescents at Hasanudin Orphanage with a research sample of 60 adolescents through non-probability sampling techniques with sampling using saturated samples. The results showed: 1) the resilience profile of the Hasanudin Orphanage youth in general was in the high category; 2) appropriate personal and social guidance services according to the considerations of BK experts and practitioners are developed with components consisting of: rational; vision and mission; description of needs; destination; action plan and program evaluation. The results of the study can be used as a reference for the development og the guidance and counseling service program in the setting of comunities in orphanages with adolescent characteristics that have optimal resilience capatibilities. Keywords: Resilience, Orphanage Youth, Personal Guidance, Social Guidance